Determination of Glucose by a Molecular Capacitor Array Based Using a 3-(Acrylamido) Phenylboronic Acid Prepared Molecularly Imprinted Polyacrylamide Cryogel. (22nd November 2021) - Sun, Pei-Xia; Han, Xiao-Jing; Chen, Li-Jie; Chen, Zu-Jia; Pan, Wen-Jin; Zhang, Qing; Wang, Jian; Yang, Chun
Abstract: A molecular capacitor array provides sensitive and selective determination of ionizable and neutral compounds. To better recognize glucose, 3-(acrylamido) phenylboronic acid (AAPBA) was used in the preparation of a molecularly imprinted polyacrylamide cryogel. The coordination of boronic acid groups and the cis-diol structure leads to high affinity between glucose and the resulting polymer. During the molecular recognition, solvent molecules (water) in the imprinted sites were replaced by glucose. Thus, significant capacitance changes were observed due to the different permittivities of glucose and water. Hence, a portable capacitive sensor was obtained to determine glucose. The sensor shows unparalleled selectivity with preparation with operation like a chromatographic column. The interfering substances were removed by filtration or washing before determination of the template with a linear range from 1.17   × 10 − 11   to 1.44   × 10 − 4 mol/L and a detection limit of 3.72   × 10 − 12 mol/L. The sensor was employed to determine glucose in biological samples without pretreatment.